Self-supporting catalytic electrode containing ternary heterojunction material, preparation method thereof and water electrolysis device

By generating a self-supporting catalytic electrode with a ternary heterojunction layer in situ on a nickel foam substrate, and combining the inner nickel hydroxide nanosheet layer and the outer cerium dioxide nanoparticle layer, the catalytic performance and stability of CeVO4 material are improved. This solves the problems of insufficient activation of active sites and slow interfacial electron transfer rate in the existing technology, and achieves efficient OER catalysis.

CN123043573APending Publication Date: 2026-11-06CHONGQING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611407082.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing rare earth vanadate material CeVO4 suffers from problems such as insufficient activation of site activity, slow interfacial electron transfer rate, and high energy barrier due to the catalytic mechanism being mainly based on adsorption evolution, making it difficult to achieve simultaneous improvement in catalytic performance and stability in the oxygen evolution reaction at the anode.

Method used

A self-supporting catalytic electrode containing ternary heterojunction material is adopted, including a nickel foam substrate and a ternary heterojunction layer generated in situ on its surface. The inner layer is a nickel hydroxide nanosheet layer, and the outer layer is a cerium dioxide and cerium vanadate nanoparticle layer. The catalytic performance is optimized by inducing electron directional transfer and lattice oxygen oxidation mechanism through the built-in electric field.

Benefits of technology

It significantly reduces the free energy barrier of the rate-determining step of OER, improves catalytic performance and stability, and has an OER overpotential as low as 330mV, which is superior to most non-precious metal catalysts and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123043573A_ABST
    Figure CN123043573A_ABST
Patent Text Reader

Abstract

The application discloses a self-supporting catalytic electrode containing ternary heterojunction material and a preparation method and a water electrolysis device thereof, and belongs to the technical field of electrocatalytic materials. The self-supporting catalytic electrode containing ternary heterojunction material has the following advantages: (1) novel structure design, strong interface bonding force, and greatly improved electrode stability; (2) multi-stage electronic regulation, a directional built-in electric field spontaneously formed in the ternary heterojunction, and dynamic adjustment of the multi-valence state of Ce 3+ / Ce 4+ and V to optimize the local electronic structure, synergistic effect with the Ni(OH)2 active site, promotion of lattice oxygen activation and introduction of the lattice oxygen oxidation (LOM) mechanism, reduction of the energy barrier of the key reaction step of OER, and significantly accelerated reaction kinetics; (3) the self-supporting catalytic electrode has excellent catalytic performance; (4) the preparation method of the self-supporting catalytic electrode is simple, low in cost and good in repeatability; and (5) the application provides a new strategy for developing high-performance rare earth vanadate-based non-noble metal oxygen evolution catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalytic materials technology, and in particular to a self-supporting catalytic electrode containing a ternary heterojunction material, its preparation method, and a water electrolysis device. Background Technology

[0002] Hydrogen energy is a clean, efficient, and zero-carbon energy carrier. Among various hydrogen production pathways, water electrolysis, using water as the sole feedstock and without any fossil fuels involved, is an ideal technological route for the large-scale and clean production of green hydrogen. The core of this technology lies in the anodic oxygen evolution reaction (OER), which involves multi-step coupled transfers and has extremely slow intrinsic kinetics. Overcoming a high reaction energy barrier results in the actual oxygen evolution overpotential being much higher than the thermodynamic theoretical value. Consequently, the actual operating voltage of industrial alkaline electrolyzers is typically high, with most of the extra electrical energy wasted as waste heat, significantly increasing the cost of green hydrogen. Furthermore, at industrial-grade high current densities (≥500 mA·cm⁻¹),… - ²) Under operating conditions, intense bubble erosion and localized strong oxidation environments can easily cause the structural collapse of the electrode catalyst layer and the dissolution of active components, leading to an exponential decline in performance. This severely restricts hydrogen production efficiency and energy consumption. High energy consumption and poor durability have become the primary bottlenecks hindering the large-scale industrial application of hydrogen production through water electrolysis.

[0003] While noble metal-based catalysts (such as RuO2 and IrO2) can overcome some of the aforementioned difficulties, they are scarce and expensive. In recent years, rare earth-based non-noble metal catalytic materials have attracted widespread attention. Among them, rare earth vanadate materials organically integrate the unique 4f electron modulation ability of rare earth elements with the stable tetragonal zircon / monazite crystal framework of vanadates, exhibiting unique advantages such as strong corrosion resistance, tunable composition, and wide catalytic window in harsh oxygen evolution environments, demonstrating unique advantages and great research potential in the field of OER catalysis. Cerium vanadate (CeVO4) is particularly noteworthy for its Ce lattice... 3+ / Ce 4+ The existence of reversible redox pairs is considered to provide excellent electron buffering capacity, i.e., this variable valence property enables it to act as an "electron sponge" at the OER potential, dynamically adjusting the surface charge state, thus making it one of the most promising non-noble metal OER candidate materials to replace noble metals.

[0004] However, single CeVO4 materials still suffer from many insurmountable drawbacks, such as insufficient activation of catalytic sites, slow interfacial electron transfer rates, and a high energy barrier due to the predominantly adsorption evolution (AEM) catalytic mechanism. Consequently, their actual catalytic performance is far lower than that of commercial noble metal catalysts (such as RuO2 and IrO2). Existing research often attempts to improve the catalytic performance of CeVO4 by constructing binary heterostructures, but the ability to regulate the electronic structure remains limited, making it difficult to simultaneously achieve Ce site activation, rapid charge transport, and optimization of the catalytic mechanism.

[0005] Therefore, there is an urgent need for a novel ternary heterojunction material to simultaneously improve the catalytic performance and stability of OER. Summary of the Invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a self-supporting catalytic electrode containing a ternary heterojunction material, its preparation method, and a water electrolysis device. The self-supporting catalytic electrode can simultaneously achieve synergistic activation of multiple active sites and optimization of the catalytic mechanism, exhibiting excellent OER catalytic performance and stability.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This invention provides a self-supporting catalytic electrode containing a ternary heterojunction material, comprising a nickel foam substrate and a ternary heterojunction layer generated in situ on its surface; The ternary heterojunction layer includes an inner nickel hydroxide nanosheet layer and an outer nanoparticle layer. The inner layer of nickel hydroxide nanosheets is connected to the nickel foam substrate; The outer nanoparticle layer includes cerium dioxide nanoparticles and cerium vanadate nanoparticles.

[0008] The inner nickel hydroxide nanosheet layer is composited with the outer nanoparticle layer, forming a heterogeneous interface in close contact between the two.

[0009] The self-supporting catalytic electrode containing the ternary heterojunction material comprises a nickel foam substrate, a nickel hydroxide nanosheet layer, and a nanoparticle layer connected in sequence. The nanoparticle layer comprises cerium dioxide nanoparticles and cerium vanadate nanoparticles, which are in a physically mixed state.

[0010] The self-supporting catalytic electrode containing ternary heterojunction material described in this invention is represented as a CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction self-supporting electrocatalytic electrode.

[0011] Preferably, the ternary heterojunction layer contains a built-in electric field extending from the nanoparticle layer to the nickel hydroxide nanosheet layer.

[0012] The built-in electric field induces electrons to be directionally transferred from the outer nanoparticle layer (CeVO4 / CeO2 nanoparticle layer) to the inner nickel hydroxide nanosheet layer (Ni(OH)2 nanosheet layer), and through Ce... 3+ / Ce 4+ The V multivalent states synergistically regulate the local electronic structure, thereby introducing the lattice oxygen oxidation (LOM) mechanism, which significantly reduces the free energy barrier of the rate-determining step of OER.

[0013] The present invention also provides a method for preparing the above-mentioned self-supporting catalytic electrode, comprising the following steps: The self-supporting catalytic electrode is obtained by immersing a nickel foam substrate in a mixed solution containing cerium nitrate hexahydrate, vanadium trichloride and water for hydrothermal reaction.

[0014] The preparation method of this invention prepares the self-supporting catalytic electrode by in-situ generation of a ternary heterojunction structure on the surface of a nickel foam substrate via a hydrothermal method (or a one-step method). The electrode structure is novel, with tight interlayer interface bonding, enabling simultaneous synergistic activation of multiple active sites (Ce). 3+ / Ce 4+ With optimization of active sites (including Ni active sites) and catalytic mechanisms, it exhibits excellent OER catalytic performance and stability.

[0015] In the self-supported catalytic electrode containing a ternary heterojunction material prepared by the above method, the nickel source of the nickel hydroxide Ni(OH)2 nanosheets comes from the nickel foam substrate; specifically, during the hydrothermal reaction, the chloride ions (Cl) in the mixed solution containing cerium nitrate hexahydrate, vanadium trichloride, and water... - Etching the foamed nickel substrate causes nickel ions (Ni) to precipitate. 2+ The nickel ions then react with hydroxide ions (OH-) in the solution. - The process involves combining these elements to form the Ni(OH)2 nanosheets in situ on the surface of a nickel foam substrate. Preferably, the hydrothermal reaction temperature is 110℃-130℃; more preferably, it is 120℃.

[0016] Preferably, the hydrothermal reaction time is 10-15 h; more preferably, it is 12 h.

[0017] The preferred holding time for the hydrothermal reaction is 1-3 hours.

[0018] The present invention does not impose any special limitation on the equipment for the hydrothermal reaction; any equipment known to those skilled in the art is acceptable.

[0019] In some specific embodiments of the present invention, the preferred equipment is a hydrothermal reactor.

[0020] The volume of the hydrothermal reactor is preferably 50 mL.

[0021] The hydrothermal reactor is selected from polytetrafluoroethylene reactors.

[0022] Preferably, the molar ratio of cerium nitrate hexahydrate to vanadium trichloride in the mixed solution is 1:1.

[0023] Preferably, the ratio of cerium nitrate hexahydrate to water is (0.2-0.3) mol: 30 L; more preferably, it is 0.24 mol: 30 L.

[0024] Preferably, the mixed solution containing cerium nitrate hexahydrate, vanadium trichloride and water is obtained by mixing cerium nitrate hexahydrate, vanadium trichloride and water at 55℃-65℃.

[0025] The preferred mixing temperature is 60°C.

[0026] In some specific embodiments of the present invention, the mixing method is stirring.

[0027] The stirring rate is preferably 4-6 r / s; in some specific embodiments of the present invention, it is preferably 5 r / s.

[0028] The mixing time is preferably 0.8-1.2 h; in some specific embodiments of the present invention, it is preferably 1 h.

[0029] The above preparation method includes post-treatment processes such as cooling, washing, and drying after the hydrothermal reaction is completed.

[0030] The present invention does not impose any particular limitation on the solvent used for washing and the method of drying; any solvent or method known to those skilled in the art is acceptable.

[0031] In some specific embodiments of the present invention, preferably, the mixture after the hydrothermal reaction is completed is naturally cooled, and then the nickel foam is taken out, washed and dried in sequence to obtain the self-supporting catalytic electrode containing the ternary heterojunction material.

[0032] The solvents used for washing include, but are not limited to, anhydrous ethanol and water.

[0033] The drying process includes, but is not limited to, vacuum drying and oven drying.

[0034] The drying temperature is preferably 55°C-65°C. In some specific embodiments of the present invention, it is preferably 60°C.

[0035] In the preparation method described in this invention, the foamed nickel is preferably pretreated foamed nickel.

[0036] The pretreatment of the pretreated nickel foam includes the following steps: The nickel foam is then ultrasonically cleaned in sequence with hydrochloric acid, water, and anhydrous ethanol, and dried to obtain the pretreated nickel foam.

[0037] The concentration of the hydrochloric acid is preferably 0.8-1.2 M. In some specific embodiments of the present invention, it is preferably 1 M.

[0038] The water is preferably deionized water.

[0039] The drying methods include, but are not limited to, vacuum drying, oven drying, and freeze drying.

[0040] In some specific embodiments of the present invention, oven drying is preferred.

[0041] The drying temperature in the oven is 50℃-70℃. In some specific embodiments of the present invention, 60℃ is preferred. The purpose of the above pretreatment is to remove the curing layer and oil stains from the surface of the nickel foam.

[0042] The present invention also provides a water electrolysis device, comprising the self-supporting catalytic electrode described above or the self-supporting catalytic electrode prepared by the above preparation method.

[0043] Preferably, the self-supporting catalytic electrode is used as the anode of the water electrolysis device.

[0044] By employing the self-supporting catalytic electrode as the anode, the anode exhibits excellent catalytic performance at 50 mAcm⁻¹. -2 The OER overpotential at current density is as low as 330 mV, at 30 mA cm⁻¹ -2 The OER overpotential at current density is as low as 258.2 mV, and its overall performance is superior to most reported non-precious metal catalysts.

[0045] Compared with the prior art, the self-supporting catalytic electrode containing ternary heterojunction material provided by the present invention includes a nickel foam substrate and a ternary heterojunction layer generated in situ on its surface; wherein, the ternary heterojunction layer includes an inner nickel hydroxide nanosheet layer and an outer nanoparticle layer; the inner nickel hydroxide nanosheet layer is connected to the nickel foam substrate; the outer nanoparticle layer includes cerium dioxide nanoparticles and cerium vanadate nanoparticles. The self-supporting catalytic electrode containing ternary heterojunction material has the following advantages: (1) Novel structural design and strong interfacial bonding force. The Ni(OH)2 nanosheet layer is generated by in-situ etching of the nickel foam substrate, and its bonding force with the substrate is extremely strong. No binder is required, which solves the problem of catalyst shedding under high current density and greatly improves the stability of the electrode; (2) It has multi-level electronic control. The directional built-in electric field spontaneously formed inside the ternary heterojunction can simultaneously activate Ce. 3+ / Ce 4+The redox pair and Ni active site enable synergistic catalysis with dual active centers, introducing a lattice oxygen oxidation (LOM) mechanism to lower the free energy barrier of the rate-determining step of OER, significantly accelerating the reaction kinetics; (3) The self-supporting catalytic electrode exhibits excellent catalytic performance at 50 mA cm⁻¹. -2 The OER overpotential at current density is as low as 330 mV, at 30 mA cm⁻¹ -2 The OER overpotential under current density is as low as 258.2mV, and its comprehensive performance is better than most reported non-noble metal catalysts; (4) The preparation method of hydrothermal reaction is simple and controllable. The in-situ growth of ternary heterojunction can be completed by one-step hydrothermal method without the need for subsequent annealing, electrodeposition and other multi-step treatments. The process is simple, low cost and good repeatability, and is suitable for large-scale industrial production; (5) This invention provides a new strategy for developing high-performance rare earth vanadate-based non-noble metal oxygen evolution catalysts by controlling the electronic structure through interface engineering. Attached Figure Description

[0046] Figure 1 for Figure 1 The XRD spectrum of Example 1; Figure 2 The images shown are SEM and EDS images from Example 1, where (a) is an SEM image with a scale bar of 300 μm, (b) is an SEM image with a scale bar of 5.00 μm, and (c) is an EDS image. Figure 3 The images are XRD and SEM images of Comparative Example 1, where (a) is the XRD image, (b) is the SEM image with a scale bar of 2.00 μm, and (c) is the SEM image with a scale bar of 20.0 μm. Figure 4 The images are XRD and SEM images of Comparative Example 2, where (a) is the XRD image, (b) is the SEM image with a scale bar of 2.00 μm, and (c) is the SEM image with a scale bar of 5.00 μm. Figure 5 The images are XRD and SEM images of Comparative Example 3, where (a) is the XRD image, (b) is the SEM image with a scale bar of 10.0 μm, and (c) is the SEM image with a scale bar of 5.00 μm. Figure 6 The XPS and Raman spectra of Example 1 and Example 1 after CV cycling are shown, where (a) (a) High-resolution XPS spectrum of CeO2 / CeVO4 / Ni(OH)2@NF before cyclic voltammetry testing; (b) High-resolution XPS spectrum of V2p of CeO2 / CeVO4 / Ni(OH)2@NF before cyclic voltammetry testing; (c) High-resolution XPS spectrum of O1s of CeO2 / CeVO4 / Ni(OH)2@NF before cyclic voltammetry testing; (d) High-resolution XPS spectrum of CeO2 / CeVO4 / Ni(OH)2@NF after cyclic voltammetry testing; (e) High-resolution XPS spectrum of V2p of CeO2 / CeVO4 / Ni(OH)2@NF after cyclic voltammetry testing; (f) High-resolution XPS spectrum of O1s of CeO2 / CeVO4 / Ni(OH)2@NF after cyclic voltammetry testing. 1s high-resolution XPS spectra, (g) represents the full XPS spectrum of CeO2 / CeVO4 / Ni(OH)2@NF material, (h) represents the Raman spectrum of CeO2 / CeVO4 / Ni(OH)2@NF before cyclic voltammetry testing, and (i) represents the Raman spectrum of CeO2 / CeVO4 / Ni(OH)2@NF after cyclic voltammetry testing; Figure 7 The electrochemical performance diagrams of the CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction prepared in Example 1 are shown below. (a) represents the LSV curve, (b) represents the overpotential curve, (c) represents the Tafel slope curve, (d) represents the impedance spectrum (EIS) curve, (e) represents the double layer capacitance (Cdl) curve, and (f)-(i) represent the CV curves of different samples at 20-120 mV / s. Detailed Implementation

[0047] To further illustrate the present invention, the following describes in detail, with reference to embodiments, the self-supporting catalytic electrode containing ternary heterojunction material, its preparation method, and the water electrolysis device provided by the present invention.

[0048] This invention provides a self-supporting catalytic electrode containing a ternary heterojunction material, comprising a nickel foam substrate and a ternary heterojunction layer generated in situ on its surface; The ternary heterojunction layer includes an inner nickel hydroxide nanosheet layer and an outer nanoparticle layer. The inner layer of nickel hydroxide nanosheets is connected to the nickel foam substrate; The outer nanoparticle layer includes cerium dioxide nanoparticles and cerium vanadate nanoparticles.

[0049] The inner nickel hydroxide nanosheet layer is composited with the outer nanoparticle layer, forming a heterogeneous interface in close contact between the two.

[0050] The self-supporting catalytic electrode containing the ternary heterojunction material comprises a nickel foam substrate, a nickel hydroxide nanosheet layer, and a nanoparticle layer connected in sequence. The nanoparticle layer comprises cerium dioxide nanoparticles and cerium vanadate nanoparticles, which are in a physically mixed state.

[0051] The self-supporting catalytic electrode containing ternary heterojunction material described in this invention is represented as a CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction self-supporting electrocatalytic electrode.

[0052] Preferably, the ternary heterojunction layer contains a built-in electric field extending from the nanoparticle layer to the nickel hydroxide nanosheet layer.

[0053] The built-in electric field induces the directional transfer of electrons from the outer nanoparticle layer (CeVO4 / CeO2 nanoparticle layer) to the inner nickel hydroxide nanosheet layer (Ni(OH)2 nanosheet layer), which can further activate Ce. 3+ / Ce 4+ The redox pair optimizes the electronic structure of Ni sites, thereby introducing a lattice oxygen oxidation (LOM) mechanism, which significantly reduces the free energy barrier of the rate-determining step of the OER.

[0054] The present invention also provides a method for preparing the above-mentioned self-supporting catalytic electrode, comprising the following steps: The self-supporting catalytic electrode is obtained by immersing a nickel foam substrate in a mixed solution containing cerium nitrate hexahydrate, vanadium trichloride and water for hydrothermal reaction.

[0055] The preparation method of this invention prepares the self-supporting catalytic electrode by in-situ generation of a ternary heterojunction structure on the surface of a nickel foam substrate via a hydrothermal method (or a one-step method). The electrode structure is novel, with tight interlayer interface bonding, enabling simultaneous synergistic activation of multiple active sites (Ce). 3+ / Ce 4+ With optimization of active sites (including Ni active sites) and catalytic mechanisms, it exhibits excellent OER catalytic performance and stability.

[0056] In the self-supported catalytic electrode containing a ternary heterojunction material prepared by the above method, the nickel source of the nickel hydroxide Ni(OH)2 nanosheets comes from the nickel foam substrate; specifically, during the hydrothermal reaction, the chloride ions (Cl) in the mixed solution containing cerium nitrate hexahydrate, vanadium trichloride, and water... - Etching the foamed nickel substrate causes nickel ions (Ni) to precipitate. 2+ The nickel ions then react with hydroxide ions (OH-) in the solution. -The process involves combining these elements to form the Ni(OH)2 nanosheets in situ on the surface of a nickel foam substrate. Preferably, the hydrothermal reaction temperature is 110℃-130℃; more preferably, it is 120℃.

[0057] Preferably, the hydrothermal reaction time is 10-15 h; more preferably, it is 12 h.

[0058] The preferred holding time for the hydrothermal reaction is 1-3 hours.

[0059] The present invention does not impose any special limitation on the equipment for the hydrothermal reaction; any equipment known to those skilled in the art is acceptable.

[0060] In some specific embodiments of the present invention, the preferred equipment is a hydrothermal reactor.

[0061] The volume of the hydrothermal reactor is preferably 50 mL.

[0062] The hydrothermal reactor is selected from polytetrafluoroethylene reactors.

[0063] Preferably, the molar ratio of cerium nitrate hexahydrate to vanadium trichloride in the mixed solution is 1:1.

[0064] Preferably, the ratio of cerium nitrate hexahydrate to water is (0.2-0.3) mol: 30 L; more preferably, it is 0.24 mol: 30 L.

[0065] Preferably, the mixed solution containing cerium nitrate hexahydrate, vanadium trichloride and water is obtained by mixing cerium nitrate hexahydrate, vanadium trichloride and water at 55℃-65℃.

[0066] The preferred mixing temperature is 60°C.

[0067] In some specific embodiments of the present invention, the mixing method is stirring.

[0068] The stirring rate is preferably 4-6 r / s; in some specific embodiments of the present invention, it is preferably 5 r / s. The stirring time is preferably 0.8-1.2 h; in some specific embodiments of the present invention, it is preferably 1 h.

[0069] The above preparation method includes post-treatment processes such as cooling, washing, and drying after the hydrothermal reaction is completed.

[0070] The present invention does not impose any particular limitation on the solvent used for washing and the method of drying; any solvent or method known to those skilled in the art is acceptable.

[0071] In some specific embodiments of the present invention, preferably, the mixture after the hydrothermal reaction is completed is naturally cooled, and then the nickel foam is taken out, washed and dried in sequence to obtain the self-supporting catalytic electrode containing the ternary heterojunction material.

[0072] The solvents used for washing include, but are not limited to, anhydrous ethanol and water.

[0073] The drying process includes, but is not limited to, vacuum drying and oven drying.

[0074] The drying temperature is preferably 55°C-65°C. In some specific embodiments of the present invention, it is preferably 60°C.

[0075] In the preparation method described in this invention, the foamed nickel is preferably pretreated foamed nickel.

[0076] The pretreatment of the pretreated nickel foam includes the following steps: The nickel foam is then ultrasonically cleaned in sequence with hydrochloric acid, water, and anhydrous ethanol, and dried to obtain the pretreated nickel foam.

[0077] The concentration of the hydrochloric acid is preferably 0.8-1.2 M. In some specific embodiments of the present invention, it is preferably 1 M. The water is preferably deionized water.

[0078] The drying methods include, but are not limited to, vacuum drying, oven drying, and freeze drying.

[0079] In some specific embodiments of the present invention, oven drying is preferred.

[0080] The drying temperature in the oven is 50℃-70℃. In some specific embodiments of the present invention, 60℃ is preferred.

[0081] The purpose of the above pretreatment is to remove the curing layer and oil stains from the surface of the nickel foam.

[0082] The present invention also provides a water electrolysis device, comprising the self-supporting catalytic electrode described above or the self-supporting catalytic electrode prepared by the above preparation method.

[0083] Preferably, the self-supporting catalytic electrode is used as the anode of the water electrolysis device.

[0084] By employing the self-supporting catalytic electrode as the anode, the anode exhibits excellent catalytic performance at 50 mAcm⁻¹. -2 The OER overpotential at current density is as low as 330 mV, at 30 mA cm⁻¹ -2 The OER overpotential at current density is as low as 258.2 mV, and its overall performance is superior to most reported non-precious metal catalysts. All raw materials used below (such as Ce(NO3)2·6H2O, VCl3, etc.) are of analytical grade.

[0085] Unless otherwise specified, all raw materials used below are commercially available products.

[0086] Example 1

[0087] Preparation of CeO2 / CeVO4 / Ni(OH)2@NF ternary heterostructure self-supported electrocatalytic electrode

[0088] (1) Pretreatment of nickel foam: 2cm×3cm nickel foam was ultrasonically cleaned for 15 minutes each with 1M hydrochloric acid, deionized water and anhydrous ethanol to remove the surface oxide layer and oil stains, and dried at 60℃ for later use.

[0089] (2) Mixing raw materials: Dissolve 0.241 mmol cerium nitrate hexahydrate and 0.241 mmol vanadium trichloride in 30 mL of deionized water, and stir in a water bath at a stirring rate of 5 r / s and a temperature of 60 °C for 1 hour until completely dissolved to obtain a mixed solution.

[0090] (3) Hydrothermal reaction: The pretreated nickel foam is immersed in the above mixed solution, transferred to a 50mL polytetrafluoroethylene reactor, placed in an oven at 120℃ for 12 hours, and kept warm for 2 hours after the reaction is completed.

[0091] (4) Post-treatment: After naturally cooling to room temperature, take out the nickel foam, wash it 3 times with anhydrous ethanol, then wash it 3 times with deionized water, and dry it in a 60℃ oven for 2 hours to obtain CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction self-supporting electrocatalytic electrode.

[0092] Comparative Example 1

[0093] Preparation of a self-supported electrocatalytic electrode containing pure CeO2 nanoparticles

[0094] Using the same method as in Example 1, except that vanadium trichloride was not added, and the other raw materials and steps remained unchanged, pure CeO2 nanoparticles were directly grown on clean nickel foam. This was used as a control sample and is represented as a pure CeO2 sample.

[0095] Comparative Example 2

[0096] Preparation of a self-supported electrocatalytic electrode containing pure CeVO4 nanoparticles

[0097] Using the same method as in Example 1, except that 0.241 mmol vanadium trichloride was replaced with 0.241 mmol ammonium metavanadate (NH4VO3), while the other raw materials and steps remained unchanged, pure CeVO4 nanoparticles were directly grown on clean nickel foam. This was used as a control sample and is represented as a pure CeVO4 sample.

[0098] Comparative Example 3

[0099] Preparation of self-supported electrocatalytic electrode containing pure Ni(OH)2 nanoparticles

[0100] Using the same method as in Example 1, except that cerium nitrate hexahydrate was not added and all other raw materials and steps remained unchanged, pure Ni(OH)2 nanosheets were directly grown on clean nickel foam. This was used as a control sample and is referred to as the pure Ni(OH)2 sample.

[0101] The performance of the self-supporting electrocatalytic electrodes prepared in Example 1 and Comparative Examples 1-3 were tested and characterized, and the results are as follows: The X-ray diffraction pattern of the CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction self-supporting electrocatalytic electrode obtained in Example 1 was determined using X-ray diffraction (XRD). Figure 1 As shown, the diffraction peaks at 19°, 33°, and 38° correspond to the (0 0 1), (1 0 0), and (1 0 1) crystal planes of Ni(OH)2, respectively (PDF No: 14-0117); the diffraction peaks at 28°, 47°, and 56° correspond to the (1 1 1), (2 2 0), and (3 11) crystal planes of CeO2, respectively (PDF No: 65-5923); and the diffraction peaks at 18°, 24°, 32°, and 49° correspond to the (1 0 1), (2 0 0), (1 1 2), and (4 0 0) crystal planes of CeVO4, respectively (PDF No: 79-1065), with no obvious impurity peaks.

[0102] Scanning electron microscopy and energy dispersive spectroscopy (SEM and EDS) characterized the CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction self-supporting electrocatalytic electrode obtained in Example 1, and the results (e.g.) Figure 2 As shown in the figure, SEM images reveal that the CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction exhibits a uniform nanoparticle morphology. The particles are uniform in size and tightly packed on the surface of the nickel foam substrate. The inner layer of nickel hydroxide (Ni(OH)2) shows a uniformly dispersed nanosheet structure on the surface of the nickel foam, while CeO2 and CeVO4 both exhibit uniform nanoparticle morphology. Furthermore, EDS elemental mapping analysis shows that Ce, V, Ni, and O are uniformly distributed across the entire surface of the catalytic material, with no obvious elemental segregation, confirming the uniform composite of the ternary heterojunction. The XRD and SEM characterization results of the pure CeO2 sample obtained in Comparative Example 1 are shown below. Figure 3As shown, the XRD pattern indicates that the characteristic diffraction peaks at 28°, 47°, and 56° correspond to the (1 1 1), (2 2 0), and (3 1 1) crystal planes of CeO2 (PDF No: 65-5923), respectively. The remaining characteristic peaks originate from the nickel foam substrate, indicating that pure-phase CeO2 nanoparticles were successfully prepared on the nickel foam surface. Furthermore, SEM images show that the pure CeO2 exhibits a large spherical particle morphology with a particle diameter of approximately 2-3 μm. Significant agglomeration exists between the particles, and these spherical particles are uniformly loaded onto the surface of the nickel foam framework.

[0103] The XRD and SEM characterization results of the pure CeVO4 sample obtained in Comparative Example 2 are as follows: Figure 4 As shown, the XRD pattern reveals that the characteristic diffraction peaks at 18°, 24°, 32°, and 49° correspond to the (1 0 1), (2 0 0), (1 1 2), and (40 0) crystal planes of CeVO4 (PDF No: 79-7065), respectively, showing good agreement with the standard card and the absence of obvious impurity peaks, indicating the successful preparation of pure-phase CeVO4 on the nickel foam surface. Furthermore, SEM images show that pure CeVO4 exhibits a flower-like aggregate morphology, composed of numerous nanoparticles with a size of approximately 2-4 μm, and is distributed throughout the nickel foam surface.

[0104] The XRD and SEM characterization results of the pure Ni(OH)2 sample obtained in Comparative Example 3 are as follows: Figure 5 As shown, the XRD pattern indicates that the characteristic diffraction peaks at 19°, 33°, and 38° correspond to the (0 0 1), (1 0 0), and (1 0 1) crystal planes of Ni(OH)₂ (PDF No: 14-0117), respectively. The remaining peaks are characteristic peaks of the nickel foam substrate, indicating that pure phase Ni(OH)₂ was successfully grown in situ on the nickel foam surface. Furthermore, SEM images show that pure Ni(OH)₂ exhibits a typical nanosheet structure. The nanosheets grow vertically on the nickel foam surface, interlacing to form a three-dimensional network structure with a large specific surface area.

[0105] This invention uses X-ray photoelectron spectroscopy (XPS) to characterize the CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction prepared in Example 1, such as... Figure 6 As shown, X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy were used to characterize the prepared CeO2 / CeVO4 / Ni(OH)2@NF@NF ternary heterostructure material to analyze the elemental composition, surface chemical valence state, oxygen defect characteristics, and structural changes before and after electrochemical cycling.

[0106] like Figure 6 As shown in (a), Ce can be observed from the figure. 3+ and Ce4+ The corresponding characteristic peaks indicate the presence of Ce on the surface of the material (the CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction prepared in Example 1). 3+ / Ce 4+ Mixed valence state. Ce 3+ The presence of species indicates that there are certain defects and electronic structure inhomogeneities in the local lattice environment of CeO2. Figure 6 (d) and Figure 6 (a) Compared to Ce after cyclic voltammetry testing 3+ and Ce 4+ The changes in the relative intensities of the relevant characteristic peaks indicate that the local chemical environment and electronic state of Ce element undergo dynamic adjustments during the electrochemical reaction. This result suggests that Ce sites possess certain variable valence characteristics and can participate in local electron transfer during the electrochemical reaction process.

[0107] like Figure 6 As shown in (b), V2p can be observed in the figure. 1 / 2 and V 2p 3 / 2 Characteristic peak, V 2p 3 / 2 The region mainly exhibits characteristic signals of high-valence V species, indicating that the V element in the material (the CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction prepared in Example 1) mainly exists in a high-valence state. Combined with... Figure 6 The mixed valence state characteristics of Ce shown in (a) indicate that the CeO2 / CeVO4 composite interface has a local electronic structure different from that of the single component. Figure 6 (e) In contrast, the V 2p spectral region after cyclic voltammetry showed characteristics related to low-valence V species while retaining characteristic signals of high-valence V species, indicating that the valence state of V changed during the electrochemical reaction. This demonstrates that the Ce and V sites in the CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction prepared in Example 1 have the ability to dynamically adjust valence states, with local electron redistribution occurring alongside the electrochemical reaction.

[0108] like Figure 6 As shown in (c), the O 1s spectral peak can be decomposed into components such as lattice oxygen, oxygen vacancy-related oxygen species, and surface-adsorbed water. Among these, the oxygen vacancy-related component exhibits a distinct characteristic signal, indicating the presence of a certain number of oxygen defects on the surface of the prepared material. Figure 6 (f) In contrast, the relative proportions of oxygen vacancy-related components changed after cyclic voltammetry testing, indicating a dynamic evolution of the oxygen defect structure on the material surface during the electrochemical reaction. Combined with... Figure 6 (d) and Figure 6The changes in the valence states of Ce and V shown in (e) suggest that the electronic state regulation of the metal center during the electrochemical reaction is related to the evolution of oxygen defects on the surface, thereby dynamically adjusting the metal-oxygen coordination environment on the material surface.

[0109] like Figure 6 As shown in (g), characteristic signals corresponding to Ce, V, Ni and O elements can be observed in the figure, which are consistent with the results of energy dispersive spectroscopy (EDS) analysis, indicating that the prepared material contains Ce, V, Ni and O elements, further proving that the CeO2 / CeVO4 / Ni(OH)2 composite structure is grown on the surface of nickel foam substrate.

[0110] like Figure 6 As shown in (h), characteristic peaks related to the lattice vibrations of the composite material appear in the figure, indicating that the material has corresponding metal-oxygen lattice vibration characteristics. Figure 6 (i) with Figure 6 Compared to (h), the peak intensity and peak shape of some Raman characteristic peaks remained basically unchanged after cyclic voltammetry testing, further proving that the composite material has a stable lattice structure.

[0111] In conclusion, Figure 6 (a)-(c) show that the prepared CeO2 / CeVO4 / Ni(OH)2@NF material already possessed Ce before the reaction. 3+ / Ce 4+ Mixed valence states, high-valence V species, and surface oxygen defect structures; Figure 6 (d)-(f) show that after cyclic voltammetry testing, the chemical valence states of Ce and V elements change dynamically, and the oxygen vacancy-related components change accordingly, indicating that there is a synergistic evolution between the Ce / V electronic state and the surface oxygen defect structure during the electrochemical reaction. Figure 6 (h) and Figure 6 (i) This further demonstrates that the composite material has a stable crystal lattice structure.

[0112] This invention employs linear sweep voltammetry, Tafel slope analysis, electrochemical impedance spectroscopy, and double-layer capacitance measurement to systematically evaluate the oxygen evolution reaction catalytic performance of the CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction prepared in Example 1 and the self-supported electrocatalytic electrodes containing single materials prepared in Comparative Examples 1-3. The results are as follows: Figure 7 As shown in (a) and (b), the LSV curves demonstrate that the current density of the ternary heterojunction described in this invention is significantly higher than that of all comparative samples at the same potential, at 30 mA. cm -2The oxygen evolution reaction overpotential at the specified current density was only 258.2 mV, far lower than that of Comparative Example 1 (400.2 mV), Comparative Example 2 (490.2 mV), and Comparative Example 3 (447.2 mV); the LSV curve also showed that the @NF ternary heterojunction described in this invention exhibited a high overpotential at 50 mA cm⁻¹. -2 The OER overpotential at current density is as low as 330mV; such as Figure 7 As shown in (c), the Tafel slope of CeO2 / CeVO4 / Ni(OH)2 is 119.7 mV. dec - ¹, significantly lower than other comparative samples, indicating a lower energy barrier for the rate-determining step and faster reaction kinetics; Figure 7 (d) Electrochemical impedance spectroscopy (EIS) shows that the surface CeO2 / CeVO4 / Ni(OH)2 exhibits the lowest charge transfer resistance and the highest interfacial electron transport efficiency, which is attributed to the spontaneous electron transfer at the interface and the accelerating effect of the built-in electric field; such as Figure 7 (e) shows that the double-layer capacitance of CeO2 / CeVO4 / Ni(OH)2 is as high as 6.5mF. cm - ², which are 1.7 times and 2.3 times that of Comparative Example 2 and Comparative Example 1, respectively, indicating that it has the largest electrochemical active area, allowing it to expose more active sites to participate in catalytic reactions. Figure 7 As shown in (g)-(i), CeO2@NF, CeVO4@NF and Ni(OH)2@NF all exhibited corresponding CV current responses at different scan rates, providing a basis for the comparison of the above Cdl and electrochemical performance.

[0113] In summary, this invention successfully prepared a CeO2 / CeVO4 / Ni(OH)2@NF ternary heterojunction self-supporting electrocatalytic electrode via a one-step hydrothermal method. This electrode has advantages such as novel structure, tight interfacial bonding, excellent catalytic performance, and good stability, and has broad application prospects in the field of water electrolysis for hydrogen production.

[0114] Compared with the prior art, the self-supporting catalytic electrode containing ternary heterojunction material provided by the present invention has the following advantages: (1) Novel structural design and strong interfacial bonding force. The Ni(OH)2 nanosheets are generated by in-situ etching of the nickel foam substrate, and their bonding force with the substrate is extremely strong. No binder is required, which solves the problem of catalyst shedding under high current density and greatly improves the stability of the electrode; (2) It has multi-level electronic control. The directional built-in electric field spontaneously formed inside the ternary heterojunction activates Ce. 3+ / Ce 4 +The synergistic catalysis of dual active sites with V multivalence changes and Ni active sites is achieved, introducing a lattice oxygen oxidation (LOM) mechanism, reducing the free energy barrier of the rate-determining step of OER, and significantly accelerating the reaction kinetics; (3) The self-supporting catalytic electrode has excellent catalytic performance, at 50 mA cm⁻¹ -2 The OER overpotential at current density is as low as 330 mV, at 30 mA cm⁻¹ -2 The OER overpotential under current density is as low as 258.2mV, and its comprehensive performance is better than most reported non-noble metal catalysts; (4) The preparation method of hydrothermal reaction is simple and controllable. The in-situ growth of ternary heterojunction can be completed by one-step hydrothermal method without the need for subsequent annealing, electrodeposition and other multi-step treatments. The process is simple, low cost and good repeatability, and is suitable for large-scale industrial production; (5) This invention provides a new strategy for developing high-performance rare earth vanadate-based non-noble metal oxygen evolution catalysts by controlling the electronic structure through interface engineering.

[0115] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. A self-supporting catalytic electrode containing a ternary heterojunction material, characterized in that, This includes a nickel foam substrate and a ternary heterojunction layer generated in situ on its surface; The ternary heterojunction layer includes an inner nickel hydroxide nanosheet layer and an outer nanoparticle layer. The inner layer of nickel hydroxide nanosheets is connected to the nickel foam substrate; The outer nanoparticle layer includes cerium dioxide nanoparticles and cerium vanadate nanoparticles.

2. The self-supporting catalytic electrode according to claim 1, characterized in that, The ternary heterojunction layer contains a built-in electric field that points from the nanoparticle layer to the nickel hydroxide nanosheet layer.

3. The method for preparing the self-supporting catalytic electrode according to claim 1 or 2, characterized in that, Includes the following steps: The self-supporting catalytic electrode is obtained by immersing a nickel foam substrate in a mixed solution containing cerium nitrate hexahydrate, vanadium trichloride and water for hydrothermal reaction.

4. The preparation method according to claim 3, characterized in that, The temperature of the hydrothermal reaction is 110℃-130℃.

5. The preparation method according to claim 4, characterized in that, The hydrothermal reaction takes 10-15 hours.

6. The preparation method according to claim 4, characterized in that, The molar ratio of cerium nitrate hexahydrate to vanadium trichloride in the mixed solution is 1:

1.

7. The preparation method according to claim 6, characterized in that, The ratio of cerium nitrate hexahydrate to water is (0.2-0.3) mol: 30 L.

8. The preparation method according to claim 7, characterized in that, The mixed solution containing cerium nitrate hexahydrate, vanadium trichloride and water is obtained by mixing cerium nitrate hexahydrate, vanadium trichloride and water at 55℃-65℃.

9. A water electrolysis device, characterized in that, The self-supporting catalytic electrode includes the self-supporting catalytic electrode as described in claim 1 or 2, or the self-supporting catalytic electrode prepared by the preparation method described in any one of claims 3-8.

10. The water electrolysis device according to claim 9, characterized in that, The self-supporting catalytic electrode serves as the anode of the water electrolysis device.